The integration of fuzzy delphi and fuzzy topsis for pharmaceutical waste treatment selection in the context of green practice - Md Radzi, Nur Hazera (2022)
Pharmaceutical waste should be treated in the best possible manner to avoid harm toward public health and the environment. Thus, green practices can be adopted in treating the waste as effectively as possible. However, research about the best treatment with green features has only been conducted in other countries and cannot be a primary reference for Malaysia due to geographical differences. Practically, an approach to model holistic decision-making for pharmaceutical waste in Malaysia context and evaluate the robustness of the model is essential. Hence, this research develops a decision-making model to select the best treatment for pharmaceutical waste in the context of green practices in Malaysia. By using a systematic literature review and experts’ opinions, a comprehensive list of criteria, sub-criteria, and treatments were successfully collected. The computation of weights for criteria and sub-criteria as well as the ranking of treatments were analysed through Fuzzy Delphi TOPSIS. The results revealed that waste immobilisation (encapsulation) is selected as the best treatment and environmental is the most important criterion as evaluated by a panel of experts. The sensitivity analysis indicated that different combinations of criteria could influence the ranking of the treatments. The developed model contributes to the related stakeholders in waste management to assist the decision-making process. It also expands the knowledge of waste treatment in the perspective of green practices and it is argued to be a trustworthy mechanism to be implemented in Malaysia.